2003
DOI: 10.1002/ps.780
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the insecticide lambda‐cyhalothrin in ditch enclosures differing in vegetation density

Abstract: Use of the insecticide lambda-cyhalothrin in agriculture may result in the contamination of water bodies, for example by spray drift. Therefore, the possible exposure of aquatic organisms to this insecticide needs to be evaluated. The exposure of the organisms may be reduced by the strong sorption of the insecticide to organic materials and its susceptibility to hydrolysis at the high pH values in the natural range. In experiments done in May and August, formulated lambda-cyhalothrin was mixed with the water b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
73
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 6 publications
8
73
0
Order By: Relevance
“…Thus, it appears that the aquatic risk profile of LCH, in terms of relative species sensitivity, population effects and community response in a complex exposure system can largely be attributed to the single active enantiomer GCH. This indicates that the fate and behavior of the active enantiomer in LCH is not dissimilar to that of the inactive enantiomer, as indicated by the rapid dissipation of GCH from the water column in our study (with 40% of dose remaining in the water column after 1 day) which was similar to that reported for LCH (Leistra et al 2003;Roessink et al 2005). Therefore, the microcosm data illustrate that the two enantiomers making up LCH have similar fate profiles, with the single enantiomer GCH demonstrating up to twice the level of toxicity to aquatic invertebrates as the racemate LCH.…”
Section: Gch and Other Model Ecosystem Studies With Pyrethroidssupporting
confidence: 90%
“…Thus, it appears that the aquatic risk profile of LCH, in terms of relative species sensitivity, population effects and community response in a complex exposure system can largely be attributed to the single active enantiomer GCH. This indicates that the fate and behavior of the active enantiomer in LCH is not dissimilar to that of the inactive enantiomer, as indicated by the rapid dissipation of GCH from the water column in our study (with 40% of dose remaining in the water column after 1 day) which was similar to that reported for LCH (Leistra et al 2003;Roessink et al 2005). Therefore, the microcosm data illustrate that the two enantiomers making up LCH have similar fate profiles, with the single enantiomer GCH demonstrating up to twice the level of toxicity to aquatic invertebrates as the racemate LCH.…”
Section: Gch and Other Model Ecosystem Studies With Pyrethroidssupporting
confidence: 90%
“…Treatments were made by pouring a carefully measured volume of treatment solution into the enclosures, after which the water column was gently stirred to mix the compound throughout the water column without disturbing the sediment. Methods of application and chemical analysis are further described in Leistra et al (2003).…”
Section: Experimental Outlinementioning
confidence: 99%
“…Brock et al (1992), for example, showed for chlorpyrifos that the mixing of the compound through the water column was strongly influenced by the vegetation structure in microcosms. For lambda-cyhalothrin, it has been demonstrated that different densities of macrophytes can have considerable influence on the fate and bioavailability of this compound (Hand et al 2001;Leistra et al 2003). Experiments with chlorpyrifos simulating different environmental conditions indicated that at higher water temperatures, and in combination with higher light intensities, dissipation rates increased (Van Wijngaarden et al 2005).…”
mentioning
confidence: 99%
See 2 more Smart Citations